Educational mismatch in the Czech Labour Market - Martina Mysíková (Review of Economic Perspectives, 2016)
Educational mismatch in labour markets is a phenomenon that has been widely analysed, mainly with respect to rising concerns about a possible oversupply of graduates. Like most European countries, the Czech Republic has experienced a boom in tertiary education in the last decade. The incidence and determinants of over- and undereducation vary substantially depending both on the mismatch measurement approach and the data source applied. Educational mismatch is also reflected in wage levels: overeducated workers have lower wages and undereducated workers have higher wages than workers with the same education whose jobs match their education level. Second, overeducated workers earn more and undereducated workers earn less than their co-workers with exactly the required level of education. The effects are qualitatively the same regardless of the data source and measurement approach applied, but their sizes differ slightly.
Keywords: 330